COMPARISON OF THE RELIGIOUS MEANING OF WATER FESTIVALS IN THAILAND AND LAOS - Lin, Tang; Darmoko, Darmoko (UI Scholars Hub, 2024)
Both Thailand and Laos are predominantly Buddhist countries, following Theravada Buddhism. Influenced by Indian Buddhism, both countries celebrate several similar festivals, such as Songkran, Makha Bucha, Visakha Bucha, and Vixakha Souvana. Among all these celebrations, Songkran is considered the most lively, and this is the focus of this article. The article compares and analyzes the culture of Songkran in Laos and Thailand, including the festival's themes, cultural significance, and activities, to highlight the similarities and differences between the two. The cultural significance found in the Water Festival primarily stems from Indian cultural influences, while the differences in meaning are attributed to the adoption of Hindu culture after it entered Thailand and Laos. In the process of integration with local culture, the festival forms a unique cultural significance. By comparing the same festival, this article reveals differences and similarities in their cultural meanings, enhancing understanding of both cultures and contributing to friendly cultural exchange between the two countries.